(untitled) (Canadian Medical Education Journal, 2024)
Background: The COVID-19 pandemic disrupted the healthcare system, affecting physician wellbeing. The consequences of reduced time spent with patients at bedside during the pandemic has not been investigated. The objectives of this study include assessing time spent with patients, physician wellbeing and patient satisfaction before and during the pandemic. Methods: A total of 182 internal medicine physicians used Hill-Rom tracking devices to measure time spent at bedside while on the teaching hospital medicine service between September 2019 and November 2020 at Cleveland Clinic in Cleveland, Ohio. Time spent before and after March 2020, the outbreak of the pandemic were compared. Physicians’ wellbeing was evaluated before and during the pandemic using the Accreditation Council for Graduate Medical Education survey. Patients’ satisfaction was assessed via the Hospital Consumer Assessment of Healthcare Providers and Systems questionnaire and correlated to bedside time. Results: From 88,661 time records collected during the 65-week study, 44,710 (50.43%) met the quality standards and were included in the analysis. The average time spent at bedside per patient before and during the pandemic was 12.12 and 7.85 minutes, respectively. Time decreased by 3.33 minutes for interns, 6.10 minutes for residents, and 2.70 minutes for staff. The pandemic correlated with physicians’ decreased vitality and meaning in work. Patients’ satisfaction did not correlate with bedside time. Conclusion: Internal medicine physicians spent less time with patients during the pandemic and had worsened vitality and satisfaction with work. Physicians’ time spent at bedside did not correlate with patients’ satisfaction.